Clonal distribution of vancomycin‐resistant Enterococcus faecium in Turkey and the new singleton ST733. Issue 12 (6th October 2020) - Erdem, Fatma; Kayacan, Cigdem; Oncul, Oral; Karagoz, Alper; Aktas, Zerrin
Abstract: Background: The aim of this study was to provide information about the spread and characteristics of the vancomycin‐resistant Enterococcus faecium isolates (VREfm) in Turkey. Methods: Seventy‐one nonduplicate consecutive isolates of VREfm were obtained from various clinical specimens of inpatients treated at university or training hospitals in seven regions of Turkey. Further characteristics included antibiotic susceptibility testing, pulsed‐field gel electrophoresis (PFGE) of SmaI‐digested genomic DNA, and multilocus sequence typing (MLST) of selected isolates. The presence of vancomycin resistance and virulence genes ( esp and hyl ) was investigated by polymerase chain reaction (PCR). Results: All VREfm isolates had MICs to vancomycin of ≥32 mg/L and contained the van A gene. The presence of esp gene was identified in 64 and hyl in eight VREfm isolates. All VREfm showed the multiresistance phenotype, including ampicillin (99%), penicillin (99%), imipenem (99%), ciprofloxacin (87%), moxifloxacin (87%), erythromycin (97%), streptomycin (86%), gentamicin (82%), tetracycline (70%), and teicoplanin (99%). All were susceptible to tigecycline while quinupristin‐dalfopristin (97%) and linezolid (93%) were the most active other agents. Analysis of the PFGE profiles showed that 53 (74.6%) VREfm isolates shared a similar electrophoretic profile, designed as type 1, and were closely related (>85%). The sequence type was identified by MLST in 44 VRE isolates with unrelated or closely related PFGE patterns. MLST revealed that nosocomial spread of VREfm resulted from dissemination of lineage C1 E faecium clones. Sequence types ST78, ST203, and ST117 were the most frequently isolated. This is the first report of ST733 around the world. Conclusions: Lineage C1 clones are disseminated among clinical VREfm isolates in seven different regions in Turkey. Regarding VREfm isolates, the worldwide epidemic strains are in circulation in Turkey.